MEMBONGKAR HISTORIOGRAFI SUFI PEREMPUAN - SYAMSIYANI, JAMALUL MUTTAQIN (Bahasa Indonesia, 2023)
In various literary histories, women are inseparable from discriminatory construction. Women's problems often attract discourse which has yet to be resolved. Women are often considered foreign, vulnerable, and subordinate, inferior. In the historical constellation of Sufism literature, women always get second place compared to men in terms of quantity. This study tries to reveal three things: first, what is called the female Sufi ritual in Sufism literature, Second, it examines the history of female Sufi marginalization. Third, look deeply into the historical roots of the formation of Sufi marginalization of women. In addition, this study has a specific purpose, namely: first, to explain the position of women in the scope of Sufism literature, why so few write Sufi women. Second, we will look at the factors underlying the marginalization of women in Sufism literature. This study uses a library research model, gathering some literature that is directly related to the themes of this study using descriptive historical analytical methods.